Cenários de pandemia de Influenza A (H1N1) 2009 no Ceará : padrões de morbimortalidade - Lemos, Daniele Rocha Queiroz (2013)
Influenza is an acute infectious disease of viral origin, universal distribution, which affects the respiratory tract. According to statistics from the World Health Organization (WHO), about 5-15% of the world population is infected with influenza virus annually. In March 2009, with change in the pattern of occurrence of influenza in Mexico, influenza virus A (H1N1), a quadruple recombinant never seen before, was identified by analyzing samples of nasopharyngeal secretions from symptomatic American children, confirming the epidemiological link with the cases in Mexico (CDC / Atlanta, 2009) and months, with sustained transmission from person to person and involvement of various countries and nations, was sparked a new pandemic. OBJECTIVES - The objectives of this study were to describe the temporal evolution, characterize the patterns of morbidity and mortality in different periods and to identify factors associated with the occurrence and severity of deaths in different phases of pandemic Influenza A (H1N1) 2009 in Ceará. METHODS - This study is a descriptive, retrospective study of cases reported and confirmed pandemic influenza (H1N1) 2009 in the state of Ceará, in the years 2009 and 2010. RESULTS AND DISCUSSION - The pandemic occurred in three small waves, one at retention phase, characterized by mild, with rapid resolution. The second two waves, the mitigation phase, with more severe cases, higher rates of hospitalization, all patients who required intensive care (ICU) and all patients who died. 615 cases were reported, 144 of these were confirmed. 55.5% were female, 30% were mixed race, 72.5% of the cases had some serious comorbidity and 40 patients required hospitalization. Hospital mortality was 20%, and mortality in the ICU was 66%. Were significant for evolution to cure or death issues related to the demand for medical care, delay in initiation of antiviral therapy, obesity, low education, use of mechanical ventilation and be hospitalized in hospitals with specialized care. CONCLUSION - The data analysis of this study allowed in-depth knowledge about the pattern of morbidity and mortality caused by pandemic influenza A (H1N1) 2009 in the state of Ceará. The study suggests that pandemic influenza A (H1N1) 2009 in this region of Brazil was magnitude lower compared to other states in other regions of the country with low incidence but high mortality rates in ICU patients.